2022
DOI: 10.1007/s10722-022-01352-3
|View full text |Cite
|
Sign up to set email alerts
|

Association mapping, trait variation, interaction and population structure analysis in cucumber (Cucumis sativus L.)

Abstract: In several regions of the world, low productivity in this crop is attributed to several factors including poor understanding of the genomic complexity of important traits associated with fruit quality and yield. Therefore, genome wide association analysis was performed for important traits using simple sequence repeats (SSR) markers. Signi cant variation was recorded for all the studied traits in 78 cucumber genotypes under two environments (open eld and net house) which indicated that the constituted associat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 37 publications
1
0
0
Order By: Relevance
“…However, the PIC value ranged from 0.06 to 0.81 (mean 0.38); slightly higher than the PIC value (3.69) reported by [31] and 0.17 reported by [37], and lower than the PIC value (4.29) reported by [19]. The presence of a slightly high level of PIC in 96 bitter gourd genotypes of the present study might be due to high cross-pollination behaviour and similar findings were reported in other cross-pollinated crops such as cucumber [38,39].…”
Section: Discussionsupporting
confidence: 63%
“…However, the PIC value ranged from 0.06 to 0.81 (mean 0.38); slightly higher than the PIC value (3.69) reported by [31] and 0.17 reported by [37], and lower than the PIC value (4.29) reported by [19]. The presence of a slightly high level of PIC in 96 bitter gourd genotypes of the present study might be due to high cross-pollination behaviour and similar findings were reported in other cross-pollinated crops such as cucumber [38,39].…”
Section: Discussionsupporting
confidence: 63%